PENGARUH PEMBERIAN INSENTIF TERHAPA KINERJA KARYAWAN DI PT. BANK RAKYAT INDONESIA (PERSERO) TBK - Andi Permana Putra; Muhammad Hufron (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTContribution of human in a compani is very importante because humans arethemain driver for the smooth running of the production process. Companyestabbblished is to achieve the goal is achieved as expected. One that the company doeswith respectto the achievement of its objectives is to improve employees workperformance with the expectation that the products achieved will increase and canmaster the wider market.The purpose of this study to analyze the influence of simultaneous financial andnon financial incentives affect the performance of imployees of PT.Bank RakyatIndonesia (Persero) Tbk, to analyze the influence of partially financial and nonfinancial incentives affect the perfomance of employees of PT.Bank Rakyat Indonesia(Persero) Tbk, and to analyze among the financial and non financial incentives thathave a dominant influence on the performance of employees of PT.Bank RakyatIndonesia (Persero)Tbk,.Population in this research is 225 employees in PT.BRI and 69 employees.Sampling technique is random sampling. Data analysis used multiple linear regressiontest F and T test. The results of the study proved financial omcentives and non financialincentives partiallysignificant effect on employee performance at PT.Bank RakyatIndonesia (Persero)tbk. Variable financial incentives and non financial incentives.Simultaneously have a significant affect on employee performance at PT.BankRakyat Indonesia (persero)Tbk, and the results of the study prove thet the variablefinancial incentive dominantinfluence on employee performance at PT.Bank RakyatIndonesiaPersero)TbkKeywords : Financial Incentives, non financial incentives performance